1992
DOI: 10.1007/bf01888501
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyomatosis of the gallbladder with subserosal fatty proliferation: CT findings in two cases

Abstract: Adenomyomatosis of the gallbladder is frequently seen in ordinary operative specimens. Subserosal fat may proliferate in the presence of adenomyomatosis, but the amount of subserosal fat may be quite variable. Typical and atypical computed tomographic (CT) findings in two cases of adenomyomatosis with subserosal fatty proliferation of the gallbladder are presented. The thick fatty layer surrounding the thickened gallbladder wall with intramural diverticula and stones, typical of CT findings, was seen in one ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…1 Oral cholecystography may reveal RAS if it maintains a patent communication with the lumen and if the RAS are large enough to create visible collections of contrast material adjacent to the lumen of the opaciˆed gallbladder. 2,3 Ultrasound appearances of adenomyomatosis had also been well described, including multiple comet tail artifacts. 4 Recent advances of spatial and temporal resolution in CT have enabled visualization of RAS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Oral cholecystography may reveal RAS if it maintains a patent communication with the lumen and if the RAS are large enough to create visible collections of contrast material adjacent to the lumen of the opaciˆed gallbladder. 2,3 Ultrasound appearances of adenomyomatosis had also been well described, including multiple comet tail artifacts. 4 Recent advances of spatial and temporal resolution in CT have enabled visualization of RAS.…”
Section: Discussionmentioning
confidence: 99%
“…They also believed that seven speciˆc changes in Jutras' classiˆcation can overlap and have a common etiology. 2 Miyake et al reported subserosal fat proliferation in adenomyomatosis on CT. 3 The cause of fat deposition is unknown; such reports suggest that fat deposition or massiveˆbrosis in lamina propria can sometimes occur in patients with adenomyomatosis. The resected specimen had a thickˆbrous layer with inˆltration of a few small round cells just under the RAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2). Fundic adenomyomatosis can bulge with excessive subserosal fat tissue of the gallbladder, producing a mass lesion (Miyake et al 1992;Shimoji et al 2001).…”
Section: Pathology Macroscopymentioning
confidence: 99%